Multiple mini-interviews for selection of newly qualified registered nurses and midwives: Candidates evaluation results. (August 2017) - Sharples, Kath; Fitzsimons, Jennifer; Edwards, Joanne; Sloane, Luke
Highlights: Longitudinal evaluation of MMI protocol Measuring reliability of MMI protocol